Search 74,375 tutors
FIND TUTORS
Ask a question
0 0

1.simplify. write in standard form 2. factor each polynomial

Tutors, please sign in to answer this question.

1 Answer

-7y2(-4y3+6y) -> factorize the coefficients we get

-7 y2 (- 2.2.y3 + 2.3.y) -> take the 2's in front out of the parenthesis

- 7.2 y2 (-2.y3 + 3.y) -> take one y in front out of the parenthesis

-14 y3 (-2 y2 + 3) -> take a minus sign -1 in front out of the parenthesis

14 y3 (2 y2 - 3)

 

For the second polynomial

15xy4+60x2y3

15 x y4 + 4.15 x2 y3 -> take 15 in front and set parenthesis

15 (x y4 + 4 x2 y3) -> take one x in front

15 x ( y4 + 4 x y3) -> take y3 in front

15 x y3 ( y + 4 x)